16 Integrated oncology and palliative care: analysis of a new 'triggers' service for lung cancer patients. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Droney, J; Kano, Y; Nevin, J; Kamal, L; Kennett, A; Oloko, R; Popat, S; Wiseman, T; Kabir, M; Perkins, M; Rathwell, I; Wood, J; et al.
Abstract : Background: Global leading cancer organisations recommend that palliative care should be available to all patients, regardless of stage of disease. We established a novel Integrated Palliative Care service ('Triggers' Service) for lung cancer outpatients. New patients are screened by oncologists using a brief palliative care referral 'Triggers' tool to identify patients who should be referred for full assessment. Assessment of palliative care need is completed using validated tools (IPOS Integrated Palliative Outcome Scale, Performance status). Aims: Evaluation of the feasibility and effectiveness of the 'Triggers' service using data collected from the initial 12 months of the service. Methods: Prospective observational service evaluation, using descriptive statistical analyses. Approved by the local Committee for Clinical Research Results: 496 eligible patients were identified, of which 433 (87%) were reviewed through the 'Triggers' service within 8 weeks of initial oncology outpatient clinic consultation. 62% (272) of patients were positive for at least one Palliative Care referral 'Trigger' tool item. IPOS and performance status data were available for 269 of these. 79% (212/269) patients had at least 1 'severe' or 'overwhelming' palliative care need. 76% (205/269) patients were performance status 0–1. At time of analysis, 120 patients had died. The median (range) time between earliest palliative care review and death/censor date was 197 days (range 3–485 days), compared to 79 (10–1315) days at baseline before establishment of 'Triggers' service. As a result of this service, the number of new patients reviewed annually by the hospital Palliative Care team increased by 30%. Conclusion/discussion: The 'Triggers service appears feasible and effective in establishing early palliative care for patients with lung cancer. Further evaluation and economic modelling is required to facilitate roll out to other tumour groups and services.